Exploring Factors Influencing Incidental Vocabulary Acquisition among EFL Students - Muh. Adnan Dzaky Setiawan; Andi Rachmawati Syarif; Faridawati (Institut Agama Islam Negeri Palopo, 2025)
This study explores the factors influencing incidental vocabulary acquisition among English as a Foreign Language (EFL) students. Employing a qualitative case study approach, the research focuses on the personal narratives and learning processes of three EFL students enrolled in a talent scouting program. Data was collected through semi-structured interviews, allowing for an in-depth exploration of individual strategies and challenges in vocabulary acquisition. Key factors identified include media and entertainment, social interactions, and classroom experiences, particularly in reading and listening contexts. Participants expressed a strong preference for incidental learning over explicit instruction, finding it more natural and contextually meaningful. However, challenges in retaining newly acquired vocabulary highlighted the need for reinforcement strategies, such as note-taking and repeated exposure, to ensure long-term retention. The study concludes that while incidental learning is beneficial, it should be complemented by deliberate strategies to maximize vocabulary retention and application in real-world situations. By integrating various learning contexts, EFL students can achieve enriched vocabulary and greater fluency in English, ultimately enhancing their confidence in using the language.